2016
DOI: 10.1016/j.freeradbiomed.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the mitochondrial matrix peptidase ClpP in muscle cells causes mitochondrial dysfunction and decreases cell proliferation

Abstract: The caseinolytic peptidase P (ClpP) is the endopeptidase component of the mitochondrial matrix ATP-dependent ClpXP protease. ClpP degrades unfolded proteins to maintain mitochondrial protein homeostasis and is involved in the initiation of the mitochondrial unfolded protein response (UPRmt). Outside of an integral role in the UPRmt, the cellular function of ClpP is not well characterized in mammalian cells. To investigate the role of ClpP in mitochondrial function, we generated C2C12 muscle cells that are defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 48 publications
4
74
0
Order By: Relevance
“…Previously, we found that knockdown of ClpP (70% reduction compared control cells) in C2C12 muscle cells increased the expression of mitochondrial fission protein dynamin‐related protein1, Drp1 . In gWAT of ClpP −/− mice, we did not see any change in the expression of fusion protein mitofusin 2 (Mfn2) or fission proteins Drp1 or Fis1 (data not shown).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Previously, we found that knockdown of ClpP (70% reduction compared control cells) in C2C12 muscle cells increased the expression of mitochondrial fission protein dynamin‐related protein1, Drp1 . In gWAT of ClpP −/− mice, we did not see any change in the expression of fusion protein mitofusin 2 (Mfn2) or fission proteins Drp1 or Fis1 (data not shown).…”
Section: Resultsmentioning
confidence: 65%
“…In our previous study in C2C12 muscle cells, we performed an acute knockdown of ClpP and found that decline in ClpP (70% down-regulation) expression can cause mitochondrial dysfunction [13]. However, in ClpP À/À mice, such an effect was not observed in skeletal muscle.…”
Section: Discussionmentioning
confidence: 95%
“…They certainly hold the key to understand the basis of the different responses. Apart from this basic relevance, our work provides novel data about the role of CLPXP, which emerges to be of important relevance for aging and specific adverse effects such as Perrault syndrome or different forms of human cancer (Fischer et al ., ; Gispert et al ., ; Jenkinson et al ., ; Cole et al ., ; Deepa et al ., ; Seo et al ., ). Studies using the P. anserina model system will continue to contribute to the elucidation of the cellular functions of this component of the mitochondrial quality control network and of its interactions with other cellular surveillance pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated reduced activity of CLPP-1 in aged cells. As a result of deficient CLPP-1, cells were shown to have numerous alterations, such as a higher amount of ROS, decreased ATP production and downregulation of fusion markers, establishing a link between protease abnormalities, energy metabolism and mitochondrial dynamics [96,97]. In addition, CLPP-1-deficient aged cells were found to have an upregulation of mTORC1 signaling markers, suggesting that the increased activation of the mTORC1/PGC-1 axis in aged-AECII reported in our study could be a response to an upstream alteration in the mitochondrial matrix proteases [98,99].…”
Section: Mitochondria In Age-related Lung Fibrosismentioning
confidence: 99%